(untitled) (Rudarsko-geološko-naftni zbornik, 2018)
This paper focuses on the investigation of the co-utilization of two major industrial waste materials, power station fly ash and red mud. Experimental studies were carried out to establish the correlation between the physical properties of a geopolymer product and a mixture composition. The effect of mechanical activation and the red mud dosage on the geopolymerisation was investigated. Geopolymerisation of mechanically activated fly ash has been carried out with various proportions of red mud ranging between 0–30 % by weight. The compressive strength of fly ash based geopoly- mer increased until 15 % of red mud addition. The optimal red mud addition in fly ash geopolymer was determined. The influence of red mud on phase composition and chemical bonds of the resulted geopolymer were determined by XRD analysis and FTIR studies. Due to the geopolymerisation reactions, new phases like hydroxy-cancrinite, faujasite and thenardite appeared in the product.